Determinants of safety behaviors: the mediating effect of predisposing factors / Siti Farhana Hasanudin - Hasanudin, Siti Farhana (2014)
Safety has become a major concern for the organizations being the source of substantial direct and indirect costs. Furthermore, the legal requirements nowadays require the employer to fulfill all the rules and regulations that have been set by the Occupational Safety and Health Act 1994. It goes the same with SMEs where it plays a vital role in the Malaysian economy and is considered to be backbone in developing the industries. The purposes of this study are to investigate the factors that influence employees’ safety behavior among SMEs manufacturing chemical products and to identify the mediating factors that will influence safety behavior at the workplace 200 questionnaires administered to the employees revealed that there is a significant relationship between the dimension of reinforcing factor (communication) with safety behavior (participation) as mediated by predisposing factor (knowledge). The dimension of predisposing factor (knowledge) also mediates the relationship between the dimensions of reinforcing factor (modeling) and safety behavior (compliance). Other interesting results found are the significant relationship between the dimensions of reinforcing factors (communication and modeling) and safety behavior (participation) mediated by the dimension of predisposing factor (beliefs). As for the dimensions of enabling factor (skills), it does have a significant relationship with safety behavior (participation) mediated by predisposing factor (knowledge), while dimension of enabling factors (resources and skills) also does have a significant relationship with safety behavior (participation) mediated by the dimension of predisposing factors (beliefs). Lastly, the result also revealed that there is a significant relationship between the dimension of enabling factor (resources) and safety behavior (participation) mediated by the dimension of predisposing factors (perceptions). Other findings are reported and recommendations for future research are put forth in this paper.